PENYULUHAN PENINGKATAN PRODUKTIVITAS USAHA KELOMPOK TANI MELALUI PENERAPAN MANAJEMEN AGRIBISNIS SYARIAH DI DESA CIARUTEUN ILIR, KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR - Tubagus Rifqy Thantawi; Mohamad Kharis Mubarok; Siti Novia Alviani (SAHID EMPOWERMENT JOURNAL, 2023)
The definition of agribusiness is a term derived from the word "Agri" which stands for Agriculture means agriculture, and "business" means business. So what is agribusiness is a business that is engaged in agriculture, especially in terms of food supply. The purpose of this community service is so that fishermen groups can find out how to run agribusiness management in a sharia manner. The method used is the presentation method. Counseling on increasing farmer group business productivity through the application of sharia agribusiness management in Desa Ciaruteun Ilir is very beneficial for farmer groups, this is evident from the enthusiasm of community groups who are quite enthusiastic in participating in counseling from start to finish.